BENGKAYANG STUDENTS' PERCEPTIONS ON THE DIFFICULTIES OF SPEAKING ENGLISH IN SPEAKING FOR SOCIAL PURPOSES CLASS - Listyani; Milani, Riski; Rudianto, Christianto (Satya Widya, 2023)
This study focused on Bengkayang students' difficulties in improving their speaking skills in the Speaking for Social Purposes class as their first speaking class. The study aimed to find out ELEP (English Language Education Program), especially Bengkayang students’ perceptions on the difficulties of speaking English in the Speaking for Social Purposes class at the Faculty of Language and Arts in Universitas Kristen Satya Wacana, in Salatiga, Central Java. The participants of this study were 21 Bengkayang students from batch 2019 who had taken the Speaking for Social Purposes class. A closed-ended, open-ended questionnaire and semi-structured interview were used to collect the data. The findings revealed that all of the students’ encountered some difficulties in speaking English such as a lack of vocabulary, nervousness, poor grammar, poor pronunciation, and less confidence. They were afraid because they had to use grammar correctly and pronounce some words in English correctly. There were also some strategies that students used to improve their English speaking ability such as speaking in front of the mirror, practicing making sentences, speaking with their friends, listening to English music, and watching English movies